Body mass index and percent body fat in goalball and movement education in male and female children with severe visual impairment - AGOPYAN, ANİ (UNIVERSITATSVERLAG ULM GMBH, 2011)
Objective: The aim of the present study was to compare 3 months percent body fat (PBF) and body mass index (BMI) in children with severe visual impairment enrolled in goalball and movement education. Methods: Participants were 24 boys and 22 girls with visual impairment, 10-15 years of age (M = 12.5 years, SD = 1.5). Skin-fold measurements were performed on the right side of the body by using Holtain((R)) calipers. Results: Both BMI and PBF reduced in boy and girl goalball players. PBF reduced in both boys and girls of movement education group; BMI increased in boys and decreased in girls. In girls, reduction in PBF was higher in goalball group than in movement education group. Conclusions: Maturation confounds these data but movement education in especially boys and goalball in especially girls may contribute physical and/or motor fitness. (C) 2011 Elsevier GmbH. All rights reserved.
Keywords: Body mass index; Body fat; Goalball; Visual impairment; PHYSICAL-FITNESS; BLIND; OBESITY